2003
DOI: 10.1192/apt.9.5.335
|View full text |Cite
|
Sign up to set email alerts
|

What should we tell people about dementia?

Abstract: This article reviews what we should tell patients and carers about dementia. The attitudes and views of patients, carers and peer groups are examined, as is the practice of doctors and other professionals working in dementia care. Factors influencing the decision to disclose the diagnosis of dementia, including the degree of certainty of the diagnosis, the degree of insight of the patient and the severity of the dementia are considered. Advantages, disadvantages and ethical issues of disclosure are discussed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In the light of the evidence available, it is surprising that a number of authors have been able to make recommendations regarding diagnostic disclosure in dementia (Post and Whitehouse, 1995;Downs, 1999;Pinner and Bouman, 2003;Wilkinson and Milne, 2003). It has, for example, been suggested that carers should be informed of the diagnosis first (Barnes, 1997); while some carers may prefer to be informed alone (Bachman et al, 2000), others may prefer the person with dementia to be present.…”
Section: Discussionmentioning
confidence: 95%
“…In the light of the evidence available, it is surprising that a number of authors have been able to make recommendations regarding diagnostic disclosure in dementia (Post and Whitehouse, 1995;Downs, 1999;Pinner and Bouman, 2003;Wilkinson and Milne, 2003). It has, for example, been suggested that carers should be informed of the diagnosis first (Barnes, 1997); while some carers may prefer to be informed alone (Bachman et al, 2000), others may prefer the person with dementia to be present.…”
Section: Discussionmentioning
confidence: 95%
“…Studies from clinic samples suggest that the majority of people with mild dementia wish to know of their diagnosis (Pinner and Bouman, 2003;De Lepelaire et al, 2004). Although we do not know so much about community samples, all practitioners should assume that the diagnosis will be discussed with the person with dementia, unless there are clear reasons not to do so.…”
Section: Communicating the Diagnosismentioning
confidence: 99%
“…A systematic review of the literature about sharing the diagnosis of dementia suggests that nonsharing or vague information about it is experienced as confusing, upsetting and difficult for some people with dementia and their families (Bamford et al, 2004). During the assessment and diagnostic process people should routinely be asked if they wish to know the diagnosis and with whom this should be shared (Pratt and Wilkinson, 2001;Pinner and Bouman, 2003).…”
Section: Communicating the Diagnosismentioning
confidence: 99%
“…It is difficult to understand the reluctance to allow autonomy to take precedence over paternalism. It is clear from the work of Pinner & Bouman (2003) that people with dementia want to have all the information regarding their diagnosis. In their study they found that 92% of patients with early dementia wished to be fully informed.…”
Section: Providing Informationmentioning
confidence: 98%